The new citizen armies : Israel's armed forces in comparative perspective - Cohen, Stuart, 1946- (BESA studies in international security., 2010)
This edited book constitutes the first detailed attempt at a comparative international analysis of the transformations that are currently affecting the composition of the Israel Defense Forces (IDF) and their place in Israeli society. Focusing primarily on deviations from the traditional norm of universal military service, the book compares the emergence of a new type of ""citizen army"" in Israel with the formats that have in recent decades become evident in other western democracies. In addition, these essays correct the conventional tendency to concentrate almost exclusivel.